Effect of Lactobacillus johnsonii Strain SQ0048 on the TLRs-MyD88/NF-κB Signaling Pathway in Bovine Vaginal Epithelial Cells - Cheng, Chao; Zhang, Linchong; Mu, Junxiang; Tian, Qiaozhen; Liu, Yanming; Ma, Xiaohong; Fu, Yanru; Liu, Zhiguo; Li, Zhenjun (Frontiers in Veterinary Science, 2021)
Vaginal inflammation is a common disease of the dairy cows’ reproductive tract. Lactic acid bacteria can combat purulent inflammation caused by pathogenic bacteria and regulate the NF-κB signaling pathway mediated by toll-like receptors (TLRs) in the inflammatory response. We studied the effect of Lactobacillus johnsonii SQ0048, an isolate with antibacterial activity, on the NF-κB signaling pathway in cow vaginal epithelial cells. Serial effectors related to the TLRs-MyD88/NF-κB signaling pathway (Tlr2, Tlr4, MyD88, Ikk, Nf-κB, Il-1β, IL-6, Tnf-ɑ, and Il-10) were detected by real-time polymerase chain reaction (RT-PCR), ELISA, and Western blot. TLR2 and TLR4 were activated by SQ0048, with increased mRNA expression levels of Tlr2 and Tlr4 in SQ0048-treated bovine vaginal epithelial cells relative to control cells (P < 0.01). SQ0048 significantly increased MyD88, IKK, and activated NF-κB in cow vaginal epithelial cells (P < 0.01). SQ0048 also significantly increased expression levels of Il-1β, Il-6, and Tnf-ɑ, and decreased expression of Il-10 (P < 0.01). These data indicated that the SQ0048 strain improved the immune function of cow vaginal epithelial cells by proper activation of the TLRs-MyD88/NF-κB signaling pathway. However, further in vivo studies are required to confirm these findings.